Interschool sciences and technologies club: an internationalization experience - Tercariol, Adriana Aparecida de Lima; Moretti, Andressa Algayer da Silva[UNESP]; Souza, Aguinaldo Robinson de [UNESP] (Univ Nove Julho, 2022)
The present article is built as a cut-off from the research project Robotics, Computational Thinking and Digital Technologies in Basic Schooling Strengthening Learnings and Competences in the Resignification of Science Teaching, which is being developed since November 2019, with funding from Conselho Nacional de Desenvolvimento Cientifico e Tecnologico - CNPq and the Brazilian Ministry of Science, Technology, Innovations and Communications - MCTI, based on the Universal Call for Projects - MCTIC/CNPq - Public Notice n degrees 05/2019 - Science in School Program - Science Education in Basic Schooling, with support from Nove de Julho University-Uninove/SP-Brazil. Presented in this article are examples from gathered experiences and obtained results, from the perspective of the young participants of this project in the second half of 2021, aiming at clarifying the possible contributions of an Interschool Science Club for campaigns of internationalization, stemming from the partnership between universities and school institutions from multiple countries (Brasil y Ecuador) involved in this research. This paper is developed based on qualitative methodology, via intervention -research.
Keywords: Education; School; Science club; Technologies; Internationalization